2015
DOI: 10.1002/anie.201411338
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Total Synthesis of (−)‐Galanthamine and (−)‐Lycoramine

Abstract: The catalytic asymmetric total syntheses of (-)-galanthamine (1) and (-)-lycoramine (2) have been achieved by using a conceptually new strategy featuring two metal-catalyzed reactions as the key steps. A new method for the construction of 3,4-fused benzofurans has been developed through a palladium-catalyzed intramolecular Larock annulation reaction, which was successfully applied to the construction of the ABD tricyclic skeleton of 1 and 2. To achieve the asymmetric synthesis of 1 and 2, a Sc(III)/N,N'-dioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“… Catalytic asymmetric total synthesis of (−)‐galanthamine 19 and (−)‐lycoramine 20 reported by Jia and co‐workers in 2015 …”
Section: Scandium‐catalyzed Asymmetric Michael Additionmentioning
confidence: 99%
See 1 more Smart Citation
“… Catalytic asymmetric total synthesis of (−)‐galanthamine 19 and (−)‐lycoramine 20 reported by Jia and co‐workers in 2015 …”
Section: Scandium‐catalyzed Asymmetric Michael Additionmentioning
confidence: 99%
“…(−)‐Galanthamine 19 has shown modest activity on acetylcholinesterase inhibition, whereas (−)‐lycoramine 20 has been used clinically for treatment of Alzheimer's disease and other diseases involving memory impairment . Synthetic studies on 19 and 20 had been reported before Jia and co‐workers published their elegant work on the catalytic asymmetric total synthesis of these natural products in 2015 (Scheme ) . Their synthesis began with reductive coupling between known aldehyde 106 and amine 107 , and this was followed by tert ‐butyloxycarbonyl (Boc) group protection.…”
Section: Scandium‐catalyzed Asymmetric Michael Additionmentioning
confidence: 99%
“…Intramolecular triple bond insertion into an Ar–PdX bond followed by O ‐cyclization has also been reported. An important example is given by the synthesis of [3,4]‐fused benzofurans, similar to that shown in Scheme for indoles, starting from 2‐iodophenols bearing a suitably placed triple bond (Scheme ) . This method was successfully applied in the asymmetric total synthesis of (–)‐galanthamine and (–)‐lycoramine alkaloids …”
Section: Pd(0)‐catalyzed Processesmentioning
confidence: 99%
“…Preparation of 3,4‐fused tricyclic benzofurans by intramolecular Larock indole synthesis starting from 2‐iodophenols bearing a suitably placed triple bond …”
Section: Pd(0)‐catalyzed Processesmentioning
confidence: 99%
“…After having used primary alcohols, the scope was extended to secondary ( 7 a ) and tertiary alcohols ( 7 b and 7 c ) yielding the products 8 a – 8 c in good to excellent yields up to 94 % (Scheme a). Slightly modified reaction conditions (tris(dibenzylideneacetone)dipalladium as Pd source and potassium carbonate as base), without further optimization, even allowed the use of a phenol moiety as nucleophile (Scheme b).…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 99%